FEMALE VICTIM – SURVIVORS OF DOMESTIC VIOLENCE: A PHENOMENOLOGICAL APPROACH - WacnangDeponio, Vilma (The journal of contemporary issues in business and government, 2021)
Domestic Violence is a social problem that need immediate attention from all members of the society. There are existing laws for the protection of women, but still, these problems pervade in many cultures nationwide. The aim of the study was to explore and analyse the dynamics among female victim-survivors in the Philippines within the context of their marriage or intimate relationship. It also described the experiences of these women in terms of reaction, consequences and coping mechanisms. A phenomenological study using in-depth interviews and document analysis was used to obtain data from eight female victim survivors. All types of abuse surfaced in the study, such as physical, sexual, psychological and economic. Results indicated the most common themes of self-blame, powerlessness, suicidal thoughts, retaliation, low self-worth and self-pity. As a consequence of the abuse, the victim’s children were most affected, which include the themes of dropping out of school, developing hatred; rebellious attitude towards their father and reservations of entering a relationship. The most common mechanism that was used by the female victim-survivors was to focus on their work.